2022
DOI: 10.21664/2238-8869.2022v11i1.p276-287
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerabilidade Ambiental ao Derramamento de Óleo em Santarém (PA)

Abstract: Derramamentos de óleo podem impactar o ambiente natural e antrópico. O objetivo do presente trabalho trata do mapeamento da vulnerabilidade ambiental ao derramamento de óleo, provenientes dos transportes fluviais, comercias e turísticos na orla da cidade de Santarém (estado do Pará). Para isso, foram utilizados como base mapas temáticos de: uso/ocupação do solo e cobertura vegetal, declividade, solo, geologia e de inundação, aplicando análise e modelagem em (SIG), através da álgebra de mapas, em categorias hie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Comparing the affected areas in the proposed scenarios with the SAO [42], referring to the studied area, the Littoral sensitivity indices recorded are practically all equal to or higher than 9 (ISL ≥ 9), often reaching ISL = 10 in long stretches. These indicate zones of high and very high vulnerability, encompassing mainly fluvial environments [43]. Thus, only these results along the coastal-estuarine zone would be enough criteria to justify similar analyses to the present study.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Comparing the affected areas in the proposed scenarios with the SAO [42], referring to the studied area, the Littoral sensitivity indices recorded are practically all equal to or higher than 9 (ISL ≥ 9), often reaching ISL = 10 in long stretches. These indicate zones of high and very high vulnerability, encompassing mainly fluvial environments [43]. Thus, only these results along the coastal-estuarine zone would be enough criteria to justify similar analyses to the present study.…”
Section: Resultssupporting
confidence: 53%
“…We believe that the scenarios generated in this research are extremely useful in the event of a similar local and unannounced disaster (flowing clay). Due to what happens with the simulated hypothetical plumes during only one tidal cycle, it was found that there would be a significant demand for urgent mitigation measures and the control necessary to contain the resulting environmental impacts [9,11,13,43].…”
Section: Resultsmentioning
confidence: 99%